Reaction coalescence of nanomaterials for chalcogenides solar cells - Lim, Hui Min (2015)
Metal chalcogenide I–III–VI2 ¬semiconductors such as CuInSe2¬, CuGaSe2, CuInS2, CuIn(SxSe1-x)2 and CuIn¬1-xGax¬Se2, with bandgap in the range of 1-2eV and high absorption coefficient 105cm-1, have attracted considerable attention as absorbers for thin film solar cells. The common methods for synthesizing I-III-VI2 nanoparticles usually require long reaction duration of up to 48hours and/or high reaction temperature of up to 700°C which limits fabrication of solar cells on flexible polymeric substrate. This project aims to synthesize I–III–VI2 ¬ nanoparticles via novel reaction pathways for solution processable thin film solar cells. The approach described in the project involves room temperature reaction coalescence of nanoparticles driven by electrostatic interactions. Firstly, we reported the systematic study of the synthesis of CuInSxSe1-x from negatively-charged CuSe nanoparticles and positively-charged In2S3 nanoparticles. The work starts with the formation of the precursors CuSe nanoparticles and In2S3 nanoparticles coated with their respective polyelectrolytes, poly(acrylic acid, sodium salt) (PAA) and poly (diallyldimethylammonium chloride) (PDAC). We investigated the role of polyelectrolytes to control surface charge and morphology of nanomaterials. The formation of CuInSxSe1-x, determined from XRD, was observed after 24 hours upon mixing these oppositely charged nanoparticles that are smaller than 20nm. In this study, the formation of CuInSxSe1-x was studied as a function of time in an effort to investigate the reaction kinetics. Raman spectroscopy and TEM images of the CuInSxSe1-x complemented the information that was derived from XRD. Control experiments indicated that the presence of specific amount of polyelectrolytes is essential for room temperature reaction coalescence to occur. From the results of Photoluminescence study, we hypothesize that desorption of the polyelectrolytes exposed the highly reactive surface of the nanoparticles, initiating the reaction between CuSe and In2S3. Photovoltaic device utilizing coalesced particles yields a power conversion efficiency of 4.9%. In an effort to further understand the conditions for room temperature reaction coalescence, we proceed to study reaction coalescence between 2 morphologically dissimilar and oppositely charged binary nanoparticles: positively-charged CuSe nanoparticles and negatively-charged In2S3 nanosheets. We attempt to understand the role of polyelectrolyte in room temperature reaction coalescence by utilizing In2S3 that are naturally negatively charged, when synthesized in the absence of polyelectrolytes. The formation of CuInSxSe1-x, determined from XRD, was also observed after 24 hours upon mixing these oppositely charged nanoparticles. This result indicates that formation of CuInSxSe1-x is also possible in the absence of bulky electrolytes on In2S3, provided that opposing surface charge is still maintained and one of the precursors is sufficiently small (<20nm). We proved that desorption of polyelectrolytes from CuSe was enabled by the presence of S2- ions surrounding the In2S3 nanosheets. Other than inducing room temperature reaction coalescence between CuSe and In2S3, there is a need to prove the feasibility of utilizing this concept for other systems. Therefore, the other focus of this work is the room temperature reaction coalescence for a system with a different chemical composition. The work starts with the formation of PDAC-CuS nanoparticles and we investigated the role of PDAC to control surface charge and morphology of CuS. We have successfully synthesized single phase CuIn5S8 by coalescing positively-charged CuS nanoparticles with negatively-charged In2S3 nanosheets at room temperature. The formation of CuIn5S8 was studied as a function of time in an effort to investigate the reaction kinetics. FT-IR spectroscopy indicates the dissociation of PDAC from CuS at the end of the reaction. Photovoltaic device utilizing coalesced particles yields a power conversion efficiency of 1.8%. The methodologies herein in reaction coalescence of quaternary systems have wide ranging prospects in compositional control at the nanoscale and possess the potential to find applications in the solar cell as well as printed electronics industries amongst others.